Valorisation of pumpkin seeds through wheat-sorghum-pumpkin seed composite flour muffins: optimization using D-optimal mixture design - Hlengiwe Mdluli; Solomon W. Kidane; T. P. Nkambule; J. S. Shelembe (Cogent Food & Agriculture)
Interest in the use of composite flours for baked products to enhance nutrition, increase the health benefit and diversify utilization of by-products is rising. This study was conducted to determine the effect of proportion of wheat, germinated sorghum and pumpkin seed flour on flour functional properties and physicochemical and sensory properties of muffins using D-optimal mixture design. The water absorption index (WAI), oil absorption index (OAI) and swelling index (SWI) were significantly (p < 0.05) influenced by the blend proportions whereas bulk density (BD) was not significantly influenced. The protein content increased with increase in the proportion of pumpkin seed flour. The fiber content increased with increase in the proportion of sorghum and pumpkin seed flour. The sensory scores decreased with increase in the proportion of sorghum and pumpkin seed flour. Preferred results were found using up to 10% pumpkin seed flour and up to 21% sorghum flour. Using numerical optimization, a combination of 83% wheat flour, 10% pumpkin seed flour and 7% sorghum flour gave best results with a desirability value of 0.621. Pumpkin seed flour can be incorporated up 10% and sorghum flour up to 7% for an acceptable product.